Evaluating the Conservation State of Naturally Aged Paper with Raman and Luminescence Spectral Mapping: Toward a Non-Destructive Diagnostic Protocol - Sabina Botti; Francesca Bonfigli; Valentina Nigro; Alessandro Rufoloni; Angelo Vannozzi (Molecules, 2022)
Micro-Raman and luminescence spectroscopy were combined with morphological analysis to study the conservation state of differently degraded paper samples, dated from 1873 to 2021. The aim of the work reported in this paper was to obtain ageing markers based on variations of Raman and fluorescence spectral features. Raman and luminescence spectra were acquired by scanning non-printed areas of books, and Raman and fluorescence maps were built by contrasting spectral parameters point by point, obtaining a micron-scale space resolved imaging of the degradation pattern. Complementary information on paper morphology and surface compactness were obtained by high-resolution scanning electron and atomic force microscopy. The proposed non-destructive procedure is particularly interesting for precious and ancient samples to analyze their degradation processes and to evaluate the performance and effectiveness of restoration treatments.